Current trends in process management in heavy oil production and refining - D. A. Pankov; A. S. Flaksman (Вестник университета, 2025)
Currently, both in the world and in Russia, new oil fi with hard-to-recover reserves are being developed. Every year the quantity of conventional oil reserves is decreasing, and their quality is deteriorating. Hard-to-recover heavy oil reserves are their alternative. The purpose of the study is to identify and analyze new promising ways of process management in oil production and refining, which mankind is forced to master in the current situation. The problematics of necessity of transition to heavy and bituminous oil reserves production and refining has been considered. The main known to date methods of heavy oil extraction have been analyzed, and advantages and disadvantages of each of them have been revealed. The characteristics of various methods of heavy oil refining, currently used, as well as the issues and prospects of their implementation have been disclosed. The refinery maintenance market has been analyzed, and the dynamics of the refi ery maintenance market volume has been given. The scheduled maintenance management segment at oil refineries has been considered separately. The volumes of Russian oil refineries maintenance market have been studied. On the basis of the study of world experience the necessity of restructuring the oil production and refining management system in Russia has been revealed. As a result of the comparative analysis the conclusions have been made about the necessity to apply not only traditionally used extraction methods, but also a promising shaft-well extraction method. The prospect of combining technologies of heavy oil refining, as well as the possibility of oil refining with the help of electric discharges has been determined.